Effect of Foliar Spray of Different Micronutrients on Plant Growth, Seed Yield and Quality in Tomato - ANILKUMAR L RAVAT; KALYANRAO PATIL; R R ACHARYA; N A PATEL (Seed Research, 2026)
A field experiment was conducted to study the effect of foliar spray of different micronutrients on plant growth, seed yield and quality in tomato at Main Vegetable Research Station, AAU, Anand and Department of Seed Science and Technology, B. A. College of Agriculture, Anand Agricultural University, Anand. The significantly higher plant height at 45, 60 and 75 DAT, mature fruits per plant, fruit yield (kg) per plant at red ripened stage, pulp to seed ratio (%), number of seeds per fruit, 1000 seed weight and seed yield per plant were recorded during kharif seasons 2020-21 and 2021-22 respectively. sSeed quality attributing characters viz.,seed germination (%), seedling length (cm), seedling dry weight (mg), SVI-I and SVI-II were found significantly higher with Boron spray @ 0.2% during both years..